Methane Adsorption in Anthracite Coal under Different Pressures and Temperatures—A Study Combining Isothermal Adsorption and Molecular Simulation - Tieya Jing; Jian Zhang; Mingyu Zhu; Wentao Zhao; Juan Zhou; Yulong Yin (Geofluids)
In situ gas content is an important parameter associating coalbed methane, while the influence of pressure and temperature on methane adsorption and desorption still needs to be revealed. In this study, the molecular structure and methane adsorption capacity of anthracite coal collected from Diandong Coalfield (China) were studied based on 13C nuclear magnetic resonance (13C NMR), Fourier transform infrared spectroscopy (FT-IR), and methane isothermal adsorption experiment. The results show that the carbon skeleton of coal sample is mainly composed by aromatic carbon (72%), followed by aliphatic carbon structure (14.2%). Carbons connected to the oxygen atoms contribute 13.7% of the total carbons in coal molecule, and the oxygen atoms are mainly in the form of carbonyl. The 2-dimension structure and 3-dimension molecular structure of coal sample was also reconstructed. The average chemical formula of the coal molecule is C200H133O21N3. The experimental methane adsorption isothermal data of the coal sample under different temperatures shows that with increasing the temperature, the methane adsorption amount at each pressure decreases obviously. At 7 MPa and 20°C, the methane adsorption amount of the coal sample is 28.5 cm3/g. Comparably, at 100°C and 7 MPa, the methane adsorption amount is only 15.9 cm3/g, decreasing by 44%. In mesopores, temperature has stronger influence on methane adsorption under higher pressure than that of lower pressure. On the contrary, in micropores, temperature has weaker effects on methane adsorption at higher pressure than that at lower pressure. The results can be beneficial for understanding methane adsorption characteristics of deep coal.